INTERNET MARKETING AS AN EFFECTIVE TOOL FOR THE DEVELOPMENT OF COMPANIES AND INCREASING THEIR MARKETING COMPETENCE (World Economics and Finance Bulletin, 2022)
The paper presents the results of the study of Internet marketing technologies application in the activities of modern companies, focused primarily on the use of IT technologies, and the problems associated with it. It characterizes the constituent elements of marketing activities carried out by using Internet technologies, describes the possibilities of development of modern business structures, focused primarily on Digital Marketing. The role of internet-marketing in promotion of goods and services by companies to the market is revealed, its efficiency is evaluated, the possibilities of growth of marketing competence of enterprises at realization of internettechnologies are described